Currency appreciation and currency attack - Imperfect common knowledge - Thu, Nguyen Anh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 28 No 2, 2012)
Abstract. This paper analyzed a model of currency attack, in which the domestic currency is pegged below its value and the real value of the currency increases gradually. The speculators, who know that the peg which might be abandoned in the future when foreign reserves reach a certain threshold can attack the currency so that the peg will collapse and the revaluation takes place immediately after the attack. The model is based on the fact that China had continuously to revalue its currency from 2005 to 2008, then in 2010, and will likely to revalue the Yuan in the near future under the pressure of its major trading partners. With the assumption of imperfect common knowledge among agents, there is a unique equilibrium in which the currency attack will occur. Keywords: Currency appreciation, currency attack, imperfect common knowledge